2011
DOI: 10.1063/1.3555177
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopic study of the negative ions of 4-thiouracil and 2,4-dithiouracil

Abstract: We report the photoelectron spectra of the negative ions of 4-thiouracil (4-TU)(-) and 2,4-dithiouracil (2,4-DTU)(-). Both of these spectra are indicative of valence anions, and they are each dominated by a single broad band with vertical detachment energies of 1.05 and 1.4 eV, respectively. Complementary calculations by Dolgounitcheva, Zakrzewski, and Ortiz (see companion paper) are in accord with our experimental results and conclude that the (4-TU)(-) and (2,4-DTU)(-) anions, reported herein, are valence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Indeed, previous studies have found both sulfur and halogen modifications of uracil to give rise to significant changes in its electronic structure. 36,37 The objective of the present study is to investigate the influence of N-substitution at the C6 position of uracil on its resulting electrophilic properties. This was revealed through the differing characteristics of the uracil versus the 6azauracil negative ions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, previous studies have found both sulfur and halogen modifications of uracil to give rise to significant changes in its electronic structure. 36,37 The objective of the present study is to investigate the influence of N-substitution at the C6 position of uracil on its resulting electrophilic properties. This was revealed through the differing characteristics of the uracil versus the 6azauracil negative ions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19 In contrast to the UV absorption spectra, not much has been reported on the photoelectron spectra of thiouracils. The main interest in this respect has been laid on the anions of these compounds, 24,25 because ionizing radiation creates anions on the way to single and double strand breaks in DNA. A single study on the tautomerism of 2TU and its methyl derivates 26 contains a static He(I) photoelectron spectrum of neutral 2TU.…”
Section: Introductionmentioning
confidence: 99%
“…25 Other relevant experiments include measurements of dissociative electron attachment to 2TU 26,27 and anion photoelectron spectroscopy of the related species 4TU − and 2,4TU − . 28 Ortiz and co-workers 29 carried out electronic structure calculations on 2TU − , obtaining results for the adiabatic electron affinity (AEA) and vertical electron affinity (VEA) for 2TU and the vertical detachment energy (VDE) of the anion; these values are 0.26, −0.17, and 0.71 eV, respectively. These numbers apply to the VB state of 2TU − in which the lowest π * orbital [Fig.…”
Section: Introductionmentioning
confidence: 99%